Language learning and language acquisition in online forums - Pramela Krish,; Supyan Hussin,; Nackeeran Sivapuniam, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Innovations in computer technology have made possible new platforms for supporting and building shared knowledge in meaningful and creative ways to enhance language learning and acquisition. Platforms like web forums, webinars, and bulletin boards in most Learner Management Systems (LMS) provide the additional platform for learning but are seldom utilized effectively to promote student interaction in language learning and acquisition. This paper reports on English Language Studies (ELS) students’ voices of how they participated and benefitted in online forums (OLFs) during their language courses. Findings from the focus group interviews with undergraduate students showed that they are more than ready to adopt OLFs as a learning platform in addition to classroom interactions. However, better effort on the part of the instructors is needed for OLFs to be beneficial. The issues that emerged in the utilization of these forums will propose future directions in the implementation of OLFs to enhance learning and acquisition among ESL students.